Elucidation of the miR164c-Guided Gene/Protein Interaction Network Controlling Seed Vigor in Rice - Huang, Kerui; Zhou, Shiqi; Shen, Kaimin; Zhou, Yan; Wang, Feng; Jiang, Xiaocheng (Frontiers in Plant Science, 2020)
MicroRNAs (miRNAs) play important roles in various aspects of plant physiology and metabolism. The expression level of miR164c is negatively correlated with seed vigor in rice (Oryza sativa L.); however, the mechanism of seed vigor regulation by miR164c remains unknown. Anti-aging capacity is an important indicator of seed vigor. Here, we report an miR164c-guided gene/protein interaction network that regulates the anti-aging ability of rice seeds. Seeds of the wild-type rice cultivar ‘Kasalath’ and its transgenic derivatives, miR164c-silenced line (MIM164c) and miR164c overexpression line (OE164c), with significant differences in anti-aging capacity, showed significant differences in gene and protein expression levels. The differentially expressed genes or proteins were significantly enriched in six metabolic functional categories related to seed vigor, including ‘stress response’, ‘protein processing in endoplasmic reticulum’, ‘embryo development’, ‘serine-type endopeptidase inhibitor’, ‘energy metabolism’, and ‘other’. Differences in the expression levels of genes or proteins related to energy metabolism, serine endopeptidase, and stress response in seeds under normal storage conditions may be associated with anti-aging capacity. The results of gene/protein interaction analyses suggest that miR164c first targets PSK5, and the PSK5 protein then interacts with the ubiquitin-associated gene RPS27AA, which simultaneously impacts the genes/proteins in the six above-mentioned functional categories. Expression levels of some of the key genes and proteins in the interaction network were verified by real-time fluorescence quantitative PCR (RT-qPCR) and multiple reaction monitoring mass spectrometry (MRM-MS), respectively. Thus, the present study provides new insights into the miRNA-mediated gene and protein interaction network that regulates seed vigor.